2019
DOI: 10.1002/lary.28334
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aquaporins in inner ear disease

Abstract: The inner ear is responsible for hearing and balance and consists of a membranous labyrinth within a bony labyrinth. The balance structure is divided into the otolith organ that recognizes linear acceleration and the semicircular canal that is responsible for rotational movement. The cochlea is the hearing organ. The external and middle ear are covered with skin and mucosa, respectively, and the space is filled with air, whereas the inner ear is composed of endolymph and perilymph. The inner ear is a fluid-fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…While these 16 miRNAs were proposed to regulate over 220 different genes within the cochlea, we narrowed our focus to gene pathways that have been shown to play a pathologic role in Menière's disease. Aquaporins are a group of intramembrane proteins that serve as water channels in various cellular processes and have been shown to potentially play a key pathogenic role in Menière's disease ( 21 , 40 ). In guinea pig models, endolymphatic hydrops can be induced through administration of vasopressin, resulting in upregulation of aquaporins ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these 16 miRNAs were proposed to regulate over 220 different genes within the cochlea, we narrowed our focus to gene pathways that have been shown to play a pathologic role in Menière's disease. Aquaporins are a group of intramembrane proteins that serve as water channels in various cellular processes and have been shown to potentially play a key pathogenic role in Menière's disease ( 21 , 40 ). In guinea pig models, endolymphatic hydrops can be induced through administration of vasopressin, resulting in upregulation of aquaporins ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is a result of our limited knowledge of the underlying pathology resulting in Menière's disease. Multiple pathophysiology mechanisms have been postulated including genetic ( 16 ), vascular ( 17 , 18 ), immunologic ( 18 20 ), aberrant aquaporin expression ( 21 ), or a combination of causes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed the presence of glucocorticoid receptors in the inner ear. The action of corticosteroids in the course of MD is based on their anti-inflammatory and immunosuppressive effects, as well as regulation of inner ear homeostasis [15][16][17]. The treatment of MD includes the use of oral dexamethasone or methylprednisolone to reduce vomiting and vestibular symptoms, particularly in cases of marked hearing loss, but there are no RCTs showing any long-term benefit of steroids in MD [16].…”
Section: Corticosteroids In Meniere's Diseasementioning
confidence: 99%
“…Among the 13 currently known AQPs, AQP1, -2, -3, -4, -5, -7, and -11 are reported to be expressed in the respiratory epithelium of the mammalian nasal cavity [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. AQPs are categorized according to their function and features: AQP1, -2, -4 and -5 are classified as orthodox AQPs; AQP3 and -7 are aquaglyceroporins; and AQP11 belongs to the unorthodox AQP group [ 4 , 5 , 6 , 7 ]. Thus, a full range of AQPs subgroups is generally expressed in the respiratory epithelium of the nasal cavity.…”
Section: Relationship Between Aqps and The Nasal Respiratory Epithmentioning
confidence: 99%
“…To date, 13 types of AQPs have been identified, named AQP0 to AQP12. These proteins have been divided into three groups based on their structural and functional characteristics: (1) orthodox AQPs (AQP0, -1, -2, -4, -5, -6, and -8), which are selectively permeable to water; (2) aquaglyceroporins (AQP3, -7, -9, and -10), which are permeable to glycerol, urea, and other small solutes, in addition to water; and (3) S-aquaporins (super- or subcellular AQP, AQP11, and -12), which have peculiar intracellular localizations and functions that are currently under investigation [ 4 , 5 , 6 , 7 ]. AQPs, which are involved in the migration of water into various cells, passively transport water across cell membranes, while also preventing the passage of ions and other solutes.…”
Section: Introductionmentioning
confidence: 99%